Citronella (Cymbopogon nardus (L.) Rendle) Leaves Infusion: Sedative Activity in Swiss-Webster Strain Male Mice - Vitamia, Cszahreyloren; Handayani, Wahyuni Mega (iora, 2024)
Insomnia is one of the sleep disorders and more severe symptoms can culminate in the onset of stress disorder. The high threat of being affected by COVID-19 causes insomnia, so drugs such as sedatives are required to treat this disorder. Research has been carried out on the sedative activity of infusion of citronella leaves (Cymbopogon nardus (L.) Rendle) in Swiss webster strains of male mice by the traction test method. The study used twenty-five mice randomly divided into five groups. Each group was given different preparations such as negative control given Na CMC 0.5%, the positive control group was given suspension of diazepam and the infusion group of citronella leaves with concentrations of 10% w/v, 30% w/v and 50% w/v as the test groups sequentially. The results showed that citronella leaves infusion had increased sedative activity along with in conjunction with an increment in test concentration. The infusion concentration of citronella leaves that have maximum sedative activity was found at a concentration of 50% w/v in the variations tested and have significantly different results compared to the control group.